Penerapan Bimbingan Konseling dalam Menentukan Jurusan Kuliah di SMA X - Husain, Aulia Shafa Kartika; Wicaksono, Awang Setiawan (Jurnal Ilmiah Psikologi (JIPSI), 2023)
Guidance counseling is the process of providing assistance by counselors to students to help students become independent individuals and make appropriate decisions. This research aims to determine the benefits of counseling in solving obstacles or problems experienced by grade 12 students who have difficulty deciding on a major. The method used in this research is a qualitative method with data collection techniques in the form of observation and interviews in providing intervention techniques in the form of counseling guidance with individual or individual counseling services and using the Elective Counseling model which is aimed at 3 grade 12 students. The results show that two out of three students have gained new views regarding the appropriate choice of major. Meanwhile, another student was still not satisfied with the counseling that had been carried out.